Carbon Nanotube-Based Glucose Biosensor: Preparation and Application - Wan, Xiyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Glucose biosensor is one of the most important sensors for converting glucose concentration into measurable signal. The use of biosensors for monitoring glucose has significant value in healthcare. It has attracted much attention in recent years because of its excellent real-time detection ability, high stability, minimally invasive and easy operation. Carrier and electron transport medium are important factors which affect the selectivity and sensitivity of biosensors. Therefore, the search for carriers with high specific surface area and excellent electrical conductivity is the key to promote the performance of glucose biosensors. Carbon nanotubes (CNTs) are excellent candidates for the modification of glucose biosensors due to their unique structure and excellent properties. In this paper, glucose biosensors are introduced briefly. The components, development, classifications and working principle of biosensors are introduced in detail. The biosensors used for detecting glucose are also outlined, including their composition, principles, development, and modifications. Especially the CNT-based sensors, which are formed by modifying the electrodes with CNTs, are described in detail. It is shown that CNTs combined with other nanomaterials could form composite materials which is very useful for improving the detection performance of glucose sensors. This work will promote real-time monitoring of glucose concentration.